2021
DOI: 10.1002/jmri.27534
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac T1 and T2 Mapping Showed Myocardial Involvement in Recovered COVID‐19 Patients Initially Considered Devoid of Cardiac Damage

Abstract: Background Myocardial injury has been found using magnetic resonance imaging in recovered coronavirus disease 2019 (COVID‐19) patients unselected or with ongoing cardiac symptoms. Purpose To evaluate for the presence of myocardial involvement in recovered COVID‐19 patients without cardiovascular symptoms and abnormal serologic markers during hospitalization. Study Type Prospective. Population Twenty‐one recovered C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(72 citation statements)
references
References 23 publications
5
67
0
Order By: Relevance
“…Hence, recent studies have assessed the presence of cardiac involvement using MRI, a noninvasive diagnostic tool, in patients infected by SARS‐CoV‐2 after recovery. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 …”
mentioning
confidence: 99%
“…Hence, recent studies have assessed the presence of cardiac involvement using MRI, a noninvasive diagnostic tool, in patients infected by SARS‐CoV‐2 after recovery. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 …”
mentioning
confidence: 99%
“…While the cohort study by Puntmann et al 1 reported a higher prevalence of findings, new studies have shown similar results to ours, although in very different populations. 23 24 McDiarmid et al 25 previously demonstrated that physiological hypertrophy slightly decreased the T1 value among highly trained athletes. We also found that, similar to other CMR parameters, men and women have distinct native T1 and T2 values, which justifies the use of sex-matched control groups when interpreting mapping alterations.…”
Section: Discussionmentioning
confidence: 96%
“…For example, myocardial edema/inflammation seen on cardiac MRI was more common in patients with severe COVID19, compared with non-severe COVID19 and healthy controls. Higher T2 signal reflective of myocardial edema was associated with markers of COVID19 severity such as D-dimer, C-reactive protein, and lymphopenia 163 . Prior history of ischemic heart disease or heart failure were associated with abnormalities on transthoracic echocardiogram in patients with COVID19 144 .…”
Section: E Predictors Of Cardiovascular Involvement In Covid19mentioning
confidence: 94%